Penciptaan Manusia Dalam Perspektif Al-Qur’an Dan Hadist Relevansinya Dengan Sains Modern - Siska Deka Sulistiya; Raisya Mayora; Alihan Satra (CV. ITTC INDONESIA, 2026)
This study aims to analyze the concept of the human sensory system from the perspective of the Qur'an and Hadith, the function of the sensory system in Islam, its relevance to modern science, and the ethical and spiritual implications of its use in the digital era. The study uses a qualitative approach with a literature study method (library research). Primary data were obtained from verses of the Qur'an and Hadith related to the sensory system, while secondary data came from books, scientific journals, and relevant academic articles. Data collection was carried out through documentation and literature review, then analyzed using a descriptive-analytical method with a thematic interpretation approach (maudhu'i). The results of the study indicate that the sensory system in the Qur'an and Hadith not only functions biologically, but also has intellectual, moral, and spiritual dimensions. In addition, the concept of the sensory system in Islam is in line with the findings of modern science, particularly in the fields of embryology, neuroscience, and psychology. The use of the sensory system in the digital era also has ethical and spiritual implications that require control in accordance with Islamic values.